Rapid identification of bear bile powder from other bile sources using chip‐based nano‐electrospray ionization tandem mass spectrometry. (22nd June 2022) - Zhang, Yixin; Wei, Jiaojiao; Li, Linnan; Liu, Yamin; Sun, Shuai; Xu, Lu; Liu, Shaoyong; Wang, Zhengtao; Yang, Li
Abstract : Rationale: Bear bile powder (BBP) is a widely used traditional Chinese medicine (TCM), and bile acids (BAs) are the main active components in BBP. Due to the scarcity of BBP resources, adulterations often occur in the market. Conventional methods to distinguish them are usually complicated and time‐consuming. To enhance effectiveness and accuracy, a rapid and rough analytical method is desperately needed. Methods: In this study, a rapid strategy using chip‐based nano‐electrospray ionization tandem mass spectrometry (nano‐ESI‐MS/MS) was established to distinguish BBP from other sources of bile powder (BP). In addition, the results were further verified by ultra‐high‐performance liquid chromatography combined with high‐resolution mass spectrometry (UPLC/MS). Results: The precision of the chip‐based nano‐ESI‐MS/MS method was validated to be acceptable with relative standard deviation (RSD) <15%. The distinction between BBP and other sources of BP, including common adulterants of pig bile powder (PBP), cattle bile powder (CBP), sheep bile powder (SBP), and chicken bile powder (CkBP), can be observed in the spectra. By using orthogonal partial least‐squares discriminant analysis (OPLS‐DA), more potential m/z markers were investigated. A BAs‐related m/z marker of 498.3 was discovered as a typical differential molecular ion peak and was identified as tauroursodeoxycholic acid (TUDCA) and taurochenodeoxycholic acid (TCDCA) in BBP. Conclusions: The proposed strategy has simple sample pretreatment steps and significantly shortened analysis time. As an emerging technology, chip‐based nano‐ESI‐MS not only provides a reference for the rapid distinction of adulterated Chinese medicines, but also provides some insights into the identification of other chemicals and foods.